Therapeutic management of the odontogenic keratocyst. An energetic approach with a conservative perspective and review of the current therapeutic options - Borrás-Ferreres, J.; Sánchez-Torres, A.; Alberdi-Navarro, J.; Aguirre-Urizar, J.; Mosqueda-Taylor, A.; Gay-Escoda, C. (Journal of clinical and experimental dentistry, 2020)
Odontogenic keratocysts (OKC) are cystic lesions appearing in the jaws, usually asymptomatic with a progressive growth into the bone. Many of them are diagnosed by a routine radiological examination. This study reports a 12-year-old girl that presented an asymptomatic large radiolucent unilocular lesion associated to the crown of 3.8 that caused displacement of the molar and the inferior alveolar canal. Differential diagnosis included OKC, unicystic ameloblastoma, ameloblastic fibroma, dentigerous cyst and orthokeratinized odontogenic cyst. Two surgical interventions were performed; first, a marsupialization, and 10 months after, the third molar extraction plus cyst enucleation, mucosa excision and the application of Carnoy's solution. The anatomopathological exam confirmed diagnosis of OKC. There was no evidence of recurrence after 2 years of follow-up. Marsupialization followed by surgical enucleation with mucosa excision and Carnoy's solution can help manage treatment of OKC, a lesion characterized by an aggressive behavior. Odontogenic keratocyst, mucosa excision, carnoy solution, third molar, tooth extraction.